(untitled) (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: Tumour markers are used clinically as an adjunct to diagnosis, staging and monitoring the prognosis of the diseases. Increased level of serum carcinoembryonic antigen (CEA) and carbohydrate antigen (CA19-9) in patients with gastric adenocarcinoma may alert the physicians about the advancement of the disease including metastasis. So, knowledge of association of serum tumour marker levels with different grades and stages of gastric adenocarcinoma may help in choosing better management option which may result in better outcome. The present study was, undertaken to find the association of CEA and CA19-9 with grades and stages of gastric adenocarcinoma. Methods: This cross-sectional analytical study was conducted in the Department of Pathology, Rajshahi Medical College over a period of two years from July 2017 to June 2019. All patients histologically confirmed of having gastric adenocarcinoma were the study population. A total of 66 patients of gastric adenocarcinoma were consecutively included in the study. In order to find the association, CEA and CA19-9 were divided into two categories at a cut-off value 10 ng/ml and 150 U/ml respectively. Accordingly, any values of CEA > 10 ng/ml and any values of CA19-9 > 150 U/ml were considered as positive for carcinoma. These cut-off values were used arbitrarily based on the findings of the previous studies. Likewise, tumour grades and stages were divided into high-grade (moderate and poorly differentiated) and low-grade (well-differentiated) and Stage I&II and stage III&IV. Then the CEA and CA19-9 values were compared between histological grades and stages. Result: The serum levels of two markers (CEA and CA19-9) were almost identically distributed between high- and low-grade tumours (p=0.871 and p=0.811 respectively). Analysis of the diagnostic accuracies demonstrated that CEA at a cut-off value of 10 ng/ml had moderate sensitivity (70.6%) and low specificity (31.2%) with overall diagnostic accuracy being 51.5%, while the CA19-9 at a cut-off value of 150 U/ml had poor sensitivity (52.9%) and poor specificity (50%) with overall diagnostic accuracy being poor (51.5%). But when the two diagnostic markers were combined together, the sensitivity sharply rose to 94%, but at the extreme compromise of specificity (3.1%). The kappa analyses revealed that the two diagnostic markers had fair agreement (22.7% agreement) in the differentiation of high-grade tumours from the low-grade ones (k-value=0.227, p=0.048). Conclusion: The study concluded that the serum levels of CEA and CA19-9 are almost similar between the high- and low-grade tumours indicating that neither of the two markers is a sensitive marker in differentiating the high-grade tumours from the low-grade ones. The sensitivity of CEA is modest, but its specificity is poor, while the CA19-9 has poor sensitivity and poor specificity with overall diagnostic accuracy being poor. When the diagnostic modalities were combined together, the sensitivity improves but at the great compromise of specificity. Ibrahim Card Med J 2021; 11 (2): 40-46